Analisis Yuridis terhadap Penerapan Hukum Pidana dalam Kasus Cyberbullying di Indonesia - Muklisin Muklisin (Prosiding Seminar Nasional Ilmu Hukum, 2024)
The rise of information and communication technology in the digital era has introduced both benefits and new challenges, one of which is cyberbullying. This study aims to analyze the application of criminal law in cyberbullying cases in Indonesia, focusing on the limitations and challenges of current regulations. Using a normative juridical method, this research examines relevant laws and court cases to evaluate how criminal law addresses cyberbullying. The findings reveal that, while certain laws provide a legal framework for tackling cyberbullying, they remain insufficient in dealing with the complexities of digital harassment. The study highlights challenges in law enforcement, including difficulties in identifying perpetrators and interpreting the law, and calls for more specific regulations and enhanced training for law enforcement officers. Increased public awareness and preventive measures are also recommended to address the issue effectively. The study's implications suggest the need for legal reform and better cooperation between institutions to improve the protection of cyberbullying victims.